2013
DOI: 10.1007/s00256-013-1784-3
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study to estimate the performance of dual-energy computed tomography for anterior cruciate ligament tears in patients with history of knee trauma

Abstract: DECT knee images with oblique sagittal reconstructions using either mixed  kV or bone removal displays (either DECT or SE) depict ACL disruption in the subacute or chronic setting with reliable identification by musculoskeletal radiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
1
27
1
1
Order By: Relevance
“…Glazebrook et al published a case-control study of 16 ACL rupture patients wherein they demonstrated DECT to have high accuracy and interobserver agreement for the detection of complete ACL tears [6]. In contrast to our study, their patient materials were chronic and subacute knee trauma patients.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Glazebrook et al published a case-control study of 16 ACL rupture patients wherein they demonstrated DECT to have high accuracy and interobserver agreement for the detection of complete ACL tears [6]. In contrast to our study, their patient materials were chronic and subacute knee trauma patients.…”
Section: Discussionmentioning
confidence: 71%
“…The main aim in this study was to determine whether a complete rupture of the cruciate ligament can be detected with DECT. In other studies, also partial ruptures were reported [5,6]. However, as most of the ACL ruptures are complete [12], our limited patient material did not allow such patient allocation to subgroups to make a reasonable statistical analysis.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations